Virus-templated FRET platform for the rational design of ratiometric fluorescent nanosensors1. Issue 50 (25th June 2015) - Chen, Limin; Wu, Yehong; Lin, Yuan; Wang, Qian
<x xml:space="preserve">Abstract</x> Based on the precise nano-architecture of bacteriophage M13, a FRET-based fluorescent nanosensor has been formulated for the ratiometric sensing of intracellular pH.